Implikasi Yuridis Pemberlakuan Peraturan Daerah Provinsi Bali Nomor 4 Tahun 2019 tentang Desa Adat di Bali - Iswantoro, Iswantoro; Tobroni, Faiq (Universitas Negeri Malang, 2023)
This study aimed to analyze the juridical implications of enforcing the Regional Regulation of the Province of Bali Number 4 of 2019 and the reconstruction of the renewal of regional regulations regarding traditional villages in Bali. This study used normative legal methods with statutory and conceptual approaches. The study results showed that the juridical implications of enforcing the Bali Province Regional Regulation Number 4 of 2019 were contrary to Government Regulation Number 38 of 2007 because it explicitly contained provisions regarding religion which should be the central government's authority. Bali Provincial Regulation Number 4 of 2019 created discrimination because it prioritized certain religious groups. Reconstruction of the renewal of regional regulations regarding traditional villages in Bali could be carried out by internalizing the tri hita karana concept, including palemahan, pawongan, dan parahyangan in the substance of regional regulations regarding traditional villages in Bali.